Les « plaisanteries » des collègues de travail : terrain d’oppression et de résistance à la violence pour les personnes LGBTQ+ - Émilie Morand; Line Chamberland; Isabel Côté; Martin Blais (Genre, Sexualité et Société)
Based on the results of an interview survey in Quebec on the factors of inclusion and exclusion of LGBTQ+ people in different areas of their lives, this article deals with an aspect that has not yet been widely exploited as a subject of study, the offensive jokes of work colleagues. These have been found to have a significant place in workplace sociability, putting LGBTQ+ people in an ambiguous position: the register of humor questions the legitimacy of reacting badly to offensive jokes. The discrepancy between the intention of the joke’s authors and the effects it may have on LGBTQ+ people gives rise to three types of reactions, ranging from turning the joke on its head to a kind of renunciation. All three types of reactions require emotional labor (Hoschild, 2003). Finally, non-heterosexual women find themselves trapped: the acceptance of their lesbianism as a factor of integration into the male social group is done at the cost of an exclusion from the group of women, making them complicit in all forms of sexism.